1999
DOI: 10.1046/j.1442-2018.1999.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese nurses’ perceptions about disclosure of information at the patients’ end of life

Abstract: Information disclosure at the end of life is one of the most debated ethical issues in Japan. This paper, using data from a larger questionnaire survey in which 147 Japanese nurses participated, describes nurses' perceptions about this issue. The nurses perceived that non-disclosure of impending death information to patients was the norm in Japan due to its traditional values. This non-disclosure of information has various impacts on clinical nurses. Tension was evident between the Japanese traditional concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…This was presumably because of Japanese nurses' experiences with insufficient pain control among cancer patients. 15 The second finding was a negative attitude of our respondents towards the acceptance of VAE. Just over 20% of the Japanese nurses thought that VAE is acceptable under certain circumstances, much fewer than reported in their western counterparts, of whom 44-75% have shown affirmative attitudes toward VAE.…”
Section: Discussionmentioning
confidence: 95%
“…This was presumably because of Japanese nurses' experiences with insufficient pain control among cancer patients. 15 The second finding was a negative attitude of our respondents towards the acceptance of VAE. Just over 20% of the Japanese nurses thought that VAE is acceptable under certain circumstances, much fewer than reported in their western counterparts, of whom 44-75% have shown affirmative attitudes toward VAE.…”
Section: Discussionmentioning
confidence: 95%
“…Research has shown that different ethnicities and cultures have different attitudes towards the communication of diagnosis and prognosis to terminally ill patients (Blackhall et al 1995;Frank et al 1998;Huang et al 1999;Konishi and Davis 1999). In the USA, for instance, various ethnic American (including Korean-, Chinese-, Mexican-, Hispanic-, African-, and European-American; Mitchell 1998) cancer patients and physicians consider complete and accurate disclosure of cancer undesirable (Hofmann et al 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Compared to African American and White elderly patients, half as many Korean Americans and Mexican Americans report wanting to be told the truth about their diagnosis, with Korean Americans and Mexican Americans preferring the family, not the patient, to be the key decisionmaker concerning EOL choices (Blackhall et al, 1999;Blackhall, Murphy, Frank, Michel, & Azen, 1995). Additionally, studies have reported preferences against patient truth-telling among seriously ill Japanese (Ito, Tanida, & Turale, 2010;Konishi & Davis, 1999), Korean (Mo et al, 2011), and to a lesser extent Chinese patients (Fielding, Wong, & Ko, 1998;Jiang et al, 2007;Orona, Koenig, & Davis, 1994). As a result, the families of these patients often become the default care decision-makers as well (Hancock et al, 2007).…”
Section: Advance Care Planningmentioning
confidence: 94%